Exploring burnout and staff turnover among acute care nurses and physicians during the COVID-19 pandemic: Insights from a qualitative assessment - Rachel L. Snyder; Katelyn A. White; Laura E. Anderson; Ronda L. Cochran (PLoS ONE, 2025)
Introduction Healthcare worker burnout and turnover are urgent issues that negatively impact workers and have the potential to impact patient care. To highlight potential factors leading to burnout and turnover among healthcare workers, focus groups were conducted with nurses and physicians who previously worked in acute care settings during the COVID-19 pandemic but have since left their careers providing direct patient care. Methods During May and June of 2023, voluntary focus groups were held over Zoom with acute care nurses and physicians who left their careers providing direct patient care. The focus groups each lasted approximately 30 minutes and included 8 or 9 participants. Open-ended prompts used to guide the discussions focused on what led participants to leave their positions and what would need to change for them to return to a role providing direct patient care. The discussions were coded by a team of coders, and then codes were grouped into corresponding themes. Participant demographics were summarized by role. Results The 49 focus group participants included 24 physicians (49%) and 25 nurses (51%). Seven convergent themes emerged during the discussions, including the mental toll of their positions, inadequate staffing, the current state of the healthcare system overall, the ways that the COVID-19 pandemic specifically made their jobs harder, support from facility administration, respect and value for their positions, and pay and incentives. Conclusions Focus group discussions held with physicians and nurses highlighted multiple factors that led to their decisions to leave their careers providing direct patient care. While more research is needed on the efficacy of specific interventions to address the issues highlighted by participants, various tools and resources are available from multiple organizations to begin to support healthcare facilities in improving the experiences of healthcare workers with the goal of preventing burnout and turnover.